The european anchovy, a genetically highly diverse species displays null within-sample haplotype diversity on a single study? - Castilho, Rita (2017)
The European anchovy has been the focus of numerous population genetic studies, most of which exposing high levels of haplotype diversity. However, Keskin and Atar (2012) revealed rather singular results of null haplotype diversities. We therefore call for caution when considering these findings.